EXPRESSION OF NEUROLOGICAL SYMPTOMATICS IN PATIENTS DEPENDING ON THE DEGREE OF SPINE DEFORMATION - Tadjiev, Mirhotam; Adambaev, Zufar; Khudayberganov, Nurmamat; Shomuratova, Gulnora; Mirzaeva, Nargiza (International Journal of Psychosocial Rehabilitation, 2020)
A survey of 337 patients with axial spinal deformities was performed. The following neurological syndromes were identified: vegetative, reflex, radicular and spinal. As the degree of spinal deformity increases, the severity of neurological changes increases. The operated patients showed a regression of neurological manifestations.